Розробка технології виготовлення нанорозмірних плівок з неоднорідною структурою методом іонно-плазмового осаджування - Normuradov, M.T.; Khozhiev, Sh.T.; Dovranov, K.T.; Davranov, Kh.T.; Davlatov, M.A.; Khollokov, F.K. (Publishing house "Academperiodika", 2023)
The study of films containing narrow-gap semiconductors is a very promising field related to the production of thermal sensors. In this work, we consider the possibility of obtaining the film coatings from silicides of Ba, Na, Ni, Co, Pd, Mn, and P and BaTiO3 using ionplasma methods. The production of film coatings from metal silicides and BaTiO3 on the surface of crystalline silicon and mica and their electronic and X-ray structural characteristics are studied. The dependence of the properties of film coatings on the conditions of the film deposition is determined.